LAJU KEHILANGAN DAN KONDISI TERKINI HABITAT BANING SULAWESI (INDOTESTUDO FORSTENII) DI SEMENANJUNG SANTIGI, SULAWESI TENGAH, INDONESIA - Riyanto, Awal; Soemarno, Suprayogo; Farajallah, Achmad (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTThe Loss and Recent Condition Habitat of Sulawesian Tortoise (Indotestudo forstenii) atCape Santigi, Central Sulawesi, Indonesia. Unsupervised method of remote sensing wasapplied were evaluated to compute the habitat loss during five years, from 2001 to 2005 usingMultispecW32 software. Meanwhile, the fieldwork was done from 22 to 30 June 2007 todetermine the recent condition of habitat at Sologi hill, a part area of Cape Santigi. During fiveyears (from 2001 to 2005) the forest (habitat) in Cape Santigi was loss making up 60.04 % (rate= 419.25 ha/year). Sologi hill forest was shown as a remaining habitat in Cape Santigi. Vegetationin Sologi hill forest is relatively still good, but is threatened by human activities. We suggesteddeveloping the natural preserve to protect this tortoise, habitat and ecosystem also otherwildlife at Sologi hill.Key words: Indotestudo forstenii, habitat, Cape Santigi, Central Sulawesi, Indonesia.